Comparisons of Copy Number, Genomic Structure, and Conserved Motifs for α-Amylase Genes from Barley, Rice, and Wheat - Zhang, Qisen; Li, Chengdao (Frontiers in Plant Science, 2017)
Barley is an important crop for the production of malt and beer. However, crops such as rice and wheat are rarely used for malting. α-amylase is the key enzyme that degrades starch during malting. In this study, we compared the genomic properties, gene copies, and conserved promoter motifs of α-amylase genes in barley, rice, and wheat. In all three crops, α-amylase consists of four subfamilies designated amy1, amy2, amy3, and amy4. In wheat and barley, members of amy1 and amy2 genes are localized on chromosomes 6 and 7, respectively. In rice, members of amy1 genes are found on chromosomes 1 and 2, and amy2 genes on chromosome 6. The barley genome has six amy1 members and three amy2 members. The wheat B genome contains four amy1 members and three amy2 members, while the rice genome has three amy1 members and one amy2 member. The B genome has mostly amy1 and amy2 members among the three wheat genomes. Amy1 promoters from all three crop genomes contain a GA-responsive complex consisting of a GA-responsive element (CAATAAA), pyrimidine box (CCTTTT) and TATCCAT/C box. This study has shown that amy1 and amy2 from both wheat and barley have similar genomic properties, including exon/intron structures and GA-responsive elements on promoters, but these differ in rice. Like barley, wheat should have sufficient amy activity to degrade starch completely during malting. Other factors, such as high protein with haze issues and the lack of husk causing Lauting difficulty, may limit the use of wheat for brewing.